2016
DOI: 10.1039/c5ra20871h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of chiral PEDOT enantiomers bearing chiral moieties in side chains: chiral recognition and its mechanism using electrochemical sensing technology

Abstract: This manuscript reports a couple of novel polymers of side-chain functionalized PEDOT. The new polymers can be employed to successfully recognize 3,4-dihydroxyphenylalanine enantiomers and we also discuss the mechanism of chiral recognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…Successive CVs of ( R )-EDTM (A) and ( S )-EDTM (B) were recorded in an aqueous LiClO 4 electrolyte at a potential scan rate of 50 mV s –1 (Figure ). The onset oxidation potentials ( E ox ) of ( R )-EDTM (0.99 V, Figure A, inset) and ( S )-EDTM (0.98 V, Figure B, inset) were essentially equal, and both were lower than that of other EDOT derivative analogues such as ( R )-/( S )-EDOT-MeCl (1.26 and 1.27 V vs Ag/AgCl), , ( R )-/( S )-EDTM-PP (1.24 and 1.14 V vs Ag/AgCl), EDOT-MeNH 2 (1.25 V vs Ag/AgCl), and C4-EDOT-COOH (1.00 V vs Ag/AgCl) . These results indicated that the introduction of a hydroxyl group reduced the E ox of ( R )-EDTM and ( S )-EDTM.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Successive CVs of ( R )-EDTM (A) and ( S )-EDTM (B) were recorded in an aqueous LiClO 4 electrolyte at a potential scan rate of 50 mV s –1 (Figure ). The onset oxidation potentials ( E ox ) of ( R )-EDTM (0.99 V, Figure A, inset) and ( S )-EDTM (0.98 V, Figure B, inset) were essentially equal, and both were lower than that of other EDOT derivative analogues such as ( R )-/( S )-EDOT-MeCl (1.26 and 1.27 V vs Ag/AgCl), , ( R )-/( S )-EDTM-PP (1.24 and 1.14 V vs Ag/AgCl), EDOT-MeNH 2 (1.25 V vs Ag/AgCl), and C4-EDOT-COOH (1.00 V vs Ag/AgCl) . These results indicated that the introduction of a hydroxyl group reduced the E ox of ( R )-EDTM and ( S )-EDTM.…”
Section: Resultsmentioning
confidence: 98%
“…( R )-/( S )-(2,3-Dihydrothieno­[3,4- b ]­[1,4]­dioxin-2-yl)­methanol (( R )-/( S )-EDTM) was synthesized as described in Scheme . ( R )-/( S )-2-(Chloromethyl)-2,3-dihydrothieno­[3,4- b ]­[1,4]­dioxine (( R )-/( S )-EDOT-MeCl) was prepared according to previously reported procedures. , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4-Alkylenedioxythiophene monomers, such as 3,4-ethylenedioxythiophene (EDOT) and 3,4-propylenedioxythiophene (ProDOT), have proven to be highly versatile platforms for functional conductive polymers ( Figure 1 ) [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ] and present many advantages over 3-hexylthiophene. Namely, the electron-donating ether substituents lower the polymer’s oxidation potential and increase its stability in the doped state [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the known methods to solve this problem are based on chromatography and capillary electrophoresis . Modified enantioselective sensors may be efficient for this, as their analytical signals depend on the isomer type …”
Section: Introductionmentioning
confidence: 99%